De uitdaging van de architectuurhistoricus (Bulletin KNOB, 2010)
This article deals with the challenges for the architectural historian as formulated by the architectural-historical domain during the past three decades. In 1977 an international symposium took place at Utrecht University in which overtures were made to social sciences. It was seen as a challenge for the architectural historian; he could become a relevant player in questions on ‘high’ and ‘low’ architecture, on preservation and selection in large-scale urban extension, renovation of social housing, increase in the building intensity of city centres and traffic interventions; the architectural historian was considered an ally of the anonymous (housing) consumer.In 1986 a symposium was held fitting in with a special issue of Archis on twenty years’ architectural-historical research in the Netherlands. In 1998 Archis returned to the subject, this time focusing on the existence of history in thinking about architecture of the past (architectural history) and the present (architectural criticism). For unlike abroad, architectural history did not play any part to speak of in the debate on architecture in the Netherlands. In 2006 the experiences of the architectural historian were evaluated on three locations at a moment when there was also much activity internationally concerning the positioning of architectural history.Speaking and writing about monuments and especially acting in this respect is less and less the exclusive field of architectural history. In modernized preservation of monuments and historic buildings as it is developing at the moment the architectural historian, with his know-how, may play various roles as a development-oriented expert and critic. With his views the architectural historian nowadays proves to be really capable of undermining the historical picture on which current architectural theory, and hence also architectural practice, are based.